1987
DOI: 10.1039/an9871200057
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurement of phenobarbital, carbamazepine, phenytoin and 5-(4-hydroxyphenyl)-5-phenylhydantoin in serum by high-performance liquid chromatography

Abstract: A rapid, highly sensitive high-performance liquid chromatographic method has been developed for the determination of phenobarbital, carbamazepine, phenytoin and its main metabolite, 544-hydroxyphenyl)-5-phenyl hydantoin, in 50 pl of serum. Serum protein was precipitated with an acetonitrile solution containing 5-(4-methylphenyl)-5-phenylhydantoin as the internal standard. The drugs were eluted from a 5 pm, C-18 reversed-phase column at 40 "C with a mobile phase consisting of an acetonitrilemethanolphosphate bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The identified drugs can then be quantified in plasma using methods described by Juergens (1986), Pang et al (1986), Mira et al (1987), Matsumoto et al (1988), Richard et al (1989) and Svinarov and Dotchev (1989) or reviewed by Burke and Thrnot (1985). Finally, several immunoassay techniques are commercially available for therapeutic drug monitoring of anticonvulsants.…”
Section: Discussionmentioning
confidence: 99%
“…The identified drugs can then be quantified in plasma using methods described by Juergens (1986), Pang et al (1986), Mira et al (1987), Matsumoto et al (1988), Richard et al (1989) and Svinarov and Dotchev (1989) or reviewed by Burke and Thrnot (1985). Finally, several immunoassay techniques are commercially available for therapeutic drug monitoring of anticonvulsants.…”
Section: Discussionmentioning
confidence: 99%
“…At 1 h prior to initiation of scanning, minipumps were surgically explanted and a blood sample withdrawn from the tail vein. Blood serum was isolated by centrifugation and stored at −20°C prior to determination of CBZ and carbamazepine‐10,11‐epoxide (CBZ‐E) concentrations by high performance liquid chromatography (HPLC) (Mira et al., 1987). At 45 min prior to initiation of scanning, animals were secured in a custom‐designed holder with an incisor bar attached to the anesthetic delivery system and injected with 18–20MBq of 125 I β‐CIT via the tail vein.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have been reported in the literature including using immunological techniques based upon fluorescence polarization immunoassay 4–6 and enzyme multiplied immunoassay (EMIT) 7, 8, gas chromatography 9–11, HPLC with UV detection 12–35, mass spectrometry 36, and techniques based upon CE on the study of phenytoin concentration of free level and/or total level in human biological samples. EMIT is a simple and rapid method for screening urine and blood for legal or illicit drugs.…”
Section: Introductionmentioning
confidence: 99%